Chinese Herbal Medicine for Mild Cognitive Impairment: A Systematic Review of Randomized Controlled Trials - Liang, Ning; Chen, Yaxin; Yang, Sihong; Liang, Changhao; Gao, Lidong; Wang, Shang; Wang, Yanping; Zhang, Zhanjun; Shi, Nannan (Frontiers in Neurology, 2022)
OBJECTIVES: This study aims to explore the benefits and harms of Chinese Herbal Medicine (CHM) for mild cognitive impairment (MCI). METHODS: Electronic searching was conducted in two English and four Chinese databases till 2021 December. Randomized clinical trials on CHM compared to no intervention, placebo or other therapies for MCI were included. RESULTS: Forty-nine RCTs (48 finished trials and 1 protocol) were identified. The overall methodological quality of included trials was relatively low. This review found that compared to no intervention or placebo, CHM can significantly decrease the number of patients who progressed to dementia (RR 0.36, 95% CI 0.22 to 0.58) and increase the cognitive function assessed by MMSE (MD 1.96, 95% CI 1.41 to 2.50) and MoCA (MD 2.44, 95% CI 1.57 to 3.31); compared to western medicine, CHM can significantly increase the score of MMSE (MD 0.88 95% CI 0.46 to 1.30) and MoCA (MD 0.87, 95% CI 0.33 to 1.41), but there was no significant difference on the score of ADL (SMD -0.61, 95% CI -1.49 to 0.27). None of the RCTs reported on the quality of life. Of 22 RCTs that reported adverse events, there was no statistical difference between the CHM and the control group. CONCLUSIONS: CHM could help to prevent progression into dementia and to improve cognitive function and ability of daily living activities. More qualified RCTs were needed to confirm the conclusion due to the low quality of current trials.